The Influence of Price, Product Quality and Service Quality on Purchase Decisions PT. Panca Asri Sentosa - Alfendo Louis; Dandy Chandra; Rosinta Romauli Situmeang (Journal of Research in Business, Economics, and Education, 2023)
Researchers took the research object at PT. Panca Asri Sentosa, due to a decrease in purchasing decisions from customers. Purchasing decision is a person's reaction to a product offered. Price, Product Quality and Service Quality are one of the reasons for the decline in purchasing decisions. The research approach used is a quantitative approach. The type of research used in this research is descriptive quantitative. In accordance with the research objectives, the nature of this research is descriptive explanatory. The population used is 133 corporate customers and the sample of this study is 100 people obtained from the Slovin formula. used to test the validity and reliability are as many as 30 customers at the same company. The results of the linear regression analysis show Purchase Decision = 4.724 + 0.298 Price + 0.763 Product Quality + 0.125 Service Quality. The results showed partially and simultaneously price, product quality and service quality partially have a significant influence on purchasing decisions at PT. Panca Asri Sentosa. The Adjusted R Square value is 0.635 which means that it implies that the effect of the independent variable on the dependent variable is 63.5% and the remaining 36.5% is the influence of other independent variables.